β-lapachone suppresses carcinogenesis of cervical cancer via interaction with AKT1 - Du, Pan; Li, Yue; Han, Anna; Wang, Mengying; Liu, Jiajing; Piao, Yingshi; Chen, Liyan (Frontiers in Pharmacology, 2025)
IntroductionCervical cancer is one of the most prevalent malignant tumors affecting women worldwide, and affected patients often face a poor prognosis due to its high drug resistance and recurrence rates. β-lapachone, a quinone compound originally extracted from natural plants, is an antitumor agent that specifically targets NQO1.MethodsCC cells were treated with varying concentrations of β-lapachone to examine its effects on glucose metabolism, proliferation, metastasis, angiogenesis, and EMT in vitro. The targets and action pathways of β-lapachone were identified using network pharmacology and molecular docking, with KEGG pathway enrichment analysis. Its effects and toxicity were verified in vivo using a nude mouse xenograft model.Resultsβ-lapachone significantly inhibited the proliferation and metastasis of cervical cancer cells by regulating glucose metabolism, reducing tumor angiogenesis, and suppressing epithelial-mesenchymal transition (EMT) in cells with high NQO1 expression. Furthermore, we identified the inactivation of the PI3K/AKT/mTOR pathway as the key mechanism underlying these effects. AKT1 was identified as a potential target of β-lapachone in modulating glucose metabolism and EMT in cervical cancer cells.ConclusionThese findings suggest that β-lapachone inhibits the malignant progression of cervical cancer by targeting AKT1 to regulate glucose metabolism in NQO1-overexpressing cells, providing a theoretical basis for developing novel therapeutic strategies for cervical cancer.